THE EFFECT OF INFLATION AND INTEREST RATE ON MSME TURNOVER IN MAKASSAR CITY - Ahmad, Muh Fajrin (SEAN Institute, 2020)
This study aims to determine the effect of inflation and interest rates on MSME turnover in Makassar City. The type of data used is secondary data from library research, both quantitative and qualitative. The population in this study is all reports on inflation and interest rates as well as reports on the turnover of the Makassar City MSME Service. The data analysis techniques used are multiple linear regression analysis, f-test, and t-test. Simultaneously the comparison between F-count and F-table which shows that F-count > F-table, indicates that the independent variables together have a significant effect on the dependent variable, so that the Inflation Rate (x1) and Interest Rate (x2) variables jointly have a significant effect on the turnover of MSMEs in Makassar City at a significant level of 5%.